SWOT Analysis as a Basis for Business Model Canvas (BMC) Development: A Case Study of PT. Guano Berkah Sejahtera - Fitra Alif Sairozie; Moh. Riza Sutjipto (Eastasouth Institute, 2026)
The increasing demand for sustainable agriculture has created significant opportunities for the development of organic-mineral fertilizer industries in Indonesia. However, fertilizer companies are required to formulate appropriate business strategies to remain competitive in an increasingly dynamic market environment. This study aims to analyze the internal and external conditions of PT. Guano Berkah Sejahtera, formulate strategic alternatives through SWOT analysis, and develop a Business Model Canvas (BMC) as a basis for business model improvement. The research employed a qualitative descriptive approach with a case study strategy. Data were collected through semi-structured interviews with internal and external stakeholders, supported by secondary data from company documents and relevant literature. The analytical tools used included Business Model Canvas, SWOT analysis, PESTEL analysis, Porter’s Five Forces, Internal Factor Evaluation (IFE), External Factor Evaluation (EFE), Internal–External (IE) Matrix, and TOWS Matrix. The results indicate that the company possesses strong internal capabilities, reflected by an IFE score of 2.77, particularly in product quality, raw material ownership, and farmer education programs. Meanwhile, the external environment presents substantial growth opportunities through the expansion of sustainable agriculture, although significant threats remain from subsidized chemical fertilizers and increasing industry competition, as reflected by an EFE score of 2.45. The IE Matrix places the company in Quadrant V (Hold and Maintain), suggesting strategies focused on market penetration and product development. The integration of SWOT and TOWS analyses generated strategic recommendations emphasizing market expansion, product innovation, digital transformation, operational efficiency, and strategic partnerships. Based on these findings, an improved Business Model Canvas was developed to support the company’s long-term competitiveness and business sustainability in the organic-mineral fertilizer industry.